James Bond: International man of gastronomy?. (1st October 2013) - Strong, Jeremy
This article is concerned with the representation of food and drink in Ian Fleming's James Bond novels. In particular, it examines how the author uses Bond's culinary knowledge and habits of consumption as an important constituent of his hero's character. Similarly, the food choices of other characters, notably villains, are shown to be linked, by Fleming, to core aspects of their identity - principally their ethnicity. Bond's impulse to observe and classify, very much in evidence in the novels' food sequences, is examined in terms of the texts' construction of Bond as a skilled identifier of signs.